From Isolation to Inclusion: Learning of the Experiences of Chinese International Students in U.S. - Will, Nancy Li (Journal of International Students, 2016)
I examined the experiences of Chinese international students in higher education and inquire about American domestic students’ perspectives on the trend of increasing numbers of Chinese international students in their institutions. In this paper, I also aim to provide suggestions on encouraging multiculturalism and inclusive academic settings within higher education.